Relation among Theology, Natural Philosophy and New Science in Giovanni Battista Riccioli (1598-1671) - Pinheiro, Maciel (Circumscribere International Journal for the History of Science, 2023)
This essay tries to analyse the way in which the Jesuit priest Giovanni Battista Riccioli (1598-1671) and his ideas were evaluated by traditional and modern Historiographies, from seventeenth to twentieth century, in secular and ecclesiastic ambiances in Italy, having in mind the possibility of historical forgetfulness of the contribution this Jesuit offered to modern science in his century. For this, the use of Contextual, Historiographical and Epistemological approaches aims to understand more deeply the man Riccioly, his ideas in the debates of his time, from his Cosmology, Jesuit Mystic, Education according to the contemporary Ratio Studiorum and Position in Jesuit Order. In fact, he established an interchange of speech among Theologians, Philosophers and Mathematicians, relating Scholastic Theology, Natural Philosophy and New Science, elaborating a solid scientific knowledge, which didn’t contradict the Holy Scriptures.